The application of inquiry-based student worksheets to enhance critical thinking skills on buffer solutions - Khairul Rizal; Meriza Faradilla (Pelita International Publishing, 2024)
This study aims to determine the effectiveness of inquiry-based learning student worksheets (LKS) in improving students' critical thinking skills on buffer solutions. One student from a class of 27 in grade XI at SMAN 1 Bireuen, Aceh, Indonesia, was selected as the sample for this research, which employed a qualitative descriptive approach. Data were collected through validated multiple-choice tests. The results indicate that inquiry-based LKS enhances students' critical thinking skills in four key aspects: questioning and answering, observing and evaluating observation reports, making decisions and considering outcomes, and drawing inductions and evaluating inductive conclusions. However, students exhibited relatively weak skills in formulating questions. Inquiry-based learning enables students to actively participate in the learning process, conduct experiments, and solve problems independently. Previous research has shown that inquiry-based learning is effective in developing critical thinking skills.